2006
DOI: 10.1007/s10562-006-0067-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-metal Catalysts for Dioxygen Reduction in an Acidic Electrolyte

Abstract: Active non-metal catalysts for the Oxygen Reduction Reaction (ORR) were prepared by decomposition of acetonitrile vapor at 900°C over a pure alumina support, and supports containing 2 wt% Fe or 2 wt% Ni on alumina. The exposed alumina and metal in the samples were subsequently washed away with HF acid to purify the solid carbon material. The sample prepared with iron was the most active sample for the ORR, with only 100 mV greater overpotential than a commercial 20 wt% Pt / Vulcan Carbon catalyst. However, nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
251
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(270 citation statements)
references
References 37 publications
17
251
0
2
Order By: Relevance
“…The stable structure of nitrogen doped CNTs and the properties of the N-doped CNTs for the dioxygen adsorption and reduction were studied. The results show that the nitrogen doping on the open-edges of carbon nanotubes is the most stable structure, that is consistent with the previous experimental results of Ozkan et al 4,5 To study the dioxygen dissociation, the minimum energy path searching based nudged elastic band (NEB) 11 method was used to calculate the dioxygen dissociation energy barrier. In the following section of this review paper, the detailed method is described.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The stable structure of nitrogen doped CNTs and the properties of the N-doped CNTs for the dioxygen adsorption and reduction were studied. The results show that the nitrogen doping on the open-edges of carbon nanotubes is the most stable structure, that is consistent with the previous experimental results of Ozkan et al 4,5 To study the dioxygen dissociation, the minimum energy path searching based nudged elastic band (NEB) 11 method was used to calculate the dioxygen dissociation energy barrier. In the following section of this review paper, the detailed method is described.…”
supporting
confidence: 88%
“…3,4 In 2006, Ozkan and coworkers reported that nitrogen-containing nanostructured carbons and nanotubes have promising catalytic activity towards ORR. 5,6 In a 2008 report, Yang et al at Argonne National Laboratory showed that the vertically-aligned CNT arrays, which are functionalized through nitrogen and iron doping by a chemical vapor deposition (CVD) process, can be electrocatalytically active toward ORR. 7 The functionalized CNTs show promise properties as an alternative non-Pt electrocatalyst with a unique nano-architecture and advantageous material properties for the cathode of PEMFC.…”
Section: Introductionmentioning
confidence: 99%
“…Although the usual reaction that occurs on carbon electrodes is far less than the four-electron reaction (O 2 + 4 H + + 4 e -→ H 2 O), there have been reports that reactions involving more electrons may take place on nitrogen-containing carbon electrodes [2][3][4][5][6]. Analyses of the ORR by a method involving a rotating ring-disk electrode showed that the ORR on CS900-AC proceeds by a 3.5-electron reaction to give about 25% of hydrogen peroxide (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13][14] In order to decrease the cost of electrocatalysts and eliminate their dependence on noble metals, various non-noble metal catalysts have been explored recently as alternatives to the Pt-based electrocatalysts, which include chalcogenide catalysts, [15][16][17][18][19] transition metal macrocyclic compounds, [20][21][22] transition metallic oxides [23][24][25][26][27] and carbon-based catalysts. [28][29][30][31][32][33][34][35] In particular, carbon-based catalysts doped with the heteroatoms such as nitrogen (N) or boron (B) have been paid much attention and been proposed as typical non-noble metal catalysts for ORR [36][37][38] in alkaline media. Especially, since Gong et al 37 reported the superior activity and stability of nitrogen doped carbon nanotube in alkaline solution, the heteroatom doped carbon materials have been expected to be promising alternative Pt-based catalysts.…”
mentioning
confidence: 99%